Proceedings 3 Parasitology research in Africa - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1997)
ProceedingsParasitology research in Africa proceedings of an IFS Workshop held in Bobo-Dioulasso, Burkina Faso from 6- 10 November 1995 edited by G Douglas Gray, Gerrit Uilenberg 1996 424pp ISBN 91 85798 452 International Foundation for Science,...